MODEL OF PRODUCTIVE WAQF POLICY GOVERNANCE FOR SUSTAINABLE ECONOMIC DEVELOPMENT: A PESTEL ANALYSIS APPROACH - AFNI REGITA CAHYANI MUIS; DR. SYAMSURI, M. SH; DR. MOHAMMAD TAQIUDDIN (Hamdard Islamicus, 2025)
This research explores the emerging role of productive Waqf as a pivotal alternative to the economic sector. Focusing on Indonesia and Malaysia as the huge potential for improving the Sharī‘ah economy, Waqf is of paramount importance in developing the financial system. Both countries have distinctive characteristics and policies governing the Waqf, albeit they have not yet maximized productive Waqf as the path to building a mechanism for a sustainable economy. Thus, the research aims to delineate the challenges and opportunities inherent in developing asset empowerment as productive Waqf. It employs a qualitative-exploratory approach and proposes a governance model for productive Waqf policies with ATLAS application. The primary data was retrieved through expert-led interviews involving academics and practitioners, including the Department of Sharī‘ah and Economics at the University of Malaya and the Division of Nazir Development and Waqf Management at the Indonesian Waqf Board. The research comprehensively maps the characteristics of both countries in managing Waqf policies encompassing government, bureaucracy, legal systems, social and economic conditions, and environmental and technological factors. This research uses PESTEL (Political, Economic, Social, Technology, Environment, and Law) and SWOT (Strength, Weakness, Opportunity, and Threat) analysis. The research finds that the productive Waqf is an effective governing policy model and a strategic pathway for every country to achieve sustainable economic development.